The Role of Socio-Cultural Competence in Teaching Foreign Languaegs - Feruza Shakirovna Kattayeva (Researchparks Publishing, 2022)
In the present study author examines the problem of development ofsocio-cultural competence in teaching foreign languages. Sociocultural competence is most often understood as: